2015
DOI: 10.18632/oncotarget.3871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RAL signal transduction in KRAS- and BRAF-mutated cells and prognostic potential of the RAL signature in colorectal cancer

Abstract: Our understanding of oncogenic signaling pathways has strongly fostered current concepts for targeted therapies in metastatic colorectal cancer. The RALA pathway is novel candidate due to its independent role in controlling expression of genes downstream of RAS.We compared RALA GTPase activities in three colorectal cancer cell lines by GTPase pull-down assay and analyzed the transcriptional and phenotypic effects of transient RALA silencing. Knocking-down RALA expression strongly diminished the active GTP-boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Current reports suggest that K-Ras may play a crucial role in regulating the progression of tumors, such as colon cancer (49) and cholangiocarcinoma (50). In addition, it can also activate multiple signaling pathways and regulate the procession of tumors (51)(52)(53). Meanwhile, the present clinical study found that not only the expression of K-Ras, PLCε, and PKCε was elevated in CRPC tissues, but K-Ras was also positively correlated with PLCε and PKCε, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…Current reports suggest that K-Ras may play a crucial role in regulating the progression of tumors, such as colon cancer (49) and cholangiocarcinoma (50). In addition, it can also activate multiple signaling pathways and regulate the procession of tumors (51)(52)(53). Meanwhile, the present clinical study found that not only the expression of K-Ras, PLCε, and PKCε was elevated in CRPC tissues, but K-Ras was also positively correlated with PLCε and PKCε, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…The p-value was determined by one-tailed Welch’s t-test, denoted in the figures as: *** for p<0.001, ** for p<0.01, and * for p<0.05. C. Kaplan–Meier survival plots in colon cancer patients with high and low levels of Ate1 mRNA of were generated utilizing a previously established database ( 21 ). The following datasets were used: GSE12945 GSE14333 GSE17538 GSE31595 GSE33114 GSE37892 GSE38832 GSE39582 and GSE41258.…”
Section: Figurementioning
confidence: 99%
“…Ras-like (Ral) GTPases include RalA and RalB, which both have differential functions (24). In several types of cancers, increased expression of RalA has been identified (25)(26)(27). Consistent with these studies, according to the GEO dataset (Access ID: GSE45016), we found increased expression levels of RalA in prostate cancer tissues.…”
Section: Discussionmentioning
confidence: 99%